Revisions to remittance trends 2007 - Ratha, Dilip; Mohapatra, Sanket; Vijayalakshmi, K. M.; Xu, Zhimei (World Bank, Washington, DC, 2012)
Revised estimates show that remittance flows to developing countries were $251 billion in 2007, up 11 percent from 2006. This Brief discusses the slowdown in remittance flows to Mexico in the first part of 2008. Remittances to countries in Latin America and the Caribbean (El Salvador, Honduras, Guatemala), and Asia (Bangladesh, Pakistan, and the Philippines) continue to grow robustly.